Hubungan Pengetahuan, Sikap Dan Peran Suami Dalam Kepatuhan Ibu Hamil Mengkonsumsi Tablet Fe Di Wilayah Kerja UPT Puskesmas Rias : Relationship between Knowledge, Attitude and Husband's Role in Pregnant Women's Compliance in Consuming Fe Tablets in the Work Area of Rias Health Center UPT - Sonata, Betaria (Indonesian Scholar Journal of Nursing and Midwifery Science, 2025)
Introduction: Anemia is a health problem that is often found throughout the world especially in the Women of Reproductive Age (WUS) group. This type of research uses quantitative research with a cross-sectional study design. The time of this research was conducted from August 2022 to February 2023. The population in this study were all pregnant women in the Rias Health Center UPT working area from January-February 2023 as many as 60 pregnant women and the total sample was the total population. Methods: Data analysis was performed using univariate and bivariate. Univariate results found that 58,3% of mothers were disobedient; 50% of mothers had less education; 66,7% had a negative attitude and 41,7% did not receive a role from their husbands. Results: The results of the bivariate analysis found that there was a significant relationship between knowledge and the mother's compliance in consuming Fe tablets (p = 0,001); there was a significant relationship between attitudes and the mother's compliance in consuming Fe tablets (p = 0,001); there was a relationship between the husband's role and the mother's compliance in consuming Fe tablets (p = 0,001). Discussion: The conclusion of this study is that the variables associated with pregnant women's compliance in consuming Fe tablets are knowledge, attitude and the role of the husband. It is suggested to the husband to pay more attention to the mother (wife) during her pregnancy by one way of supporting pregnant women to consume Fe tablets regularly.